2008
DOI: 10.1073/pnas.0708474105
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the hypoxia-inducible factor-1α pathway accelerates bone regeneration

Abstract: The hypoxia-inducible factor-1alpha (HIF-1alpha) pathway is the central regulator of adaptive responses to low oxygen availability and is required for normal skeletal development. Here, we demonstrate that the HIF-1alpha pathway is activated during bone repair and can be manipulated genetically and pharmacologically to improve skeletal healing. Mice lacking pVHL in osteoblasts with constitutive HIF-1alpha activation in osteoblasts had markedly increased vascularity and produced more bone in response to distrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
456
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 462 publications
(477 citation statements)
references
References 51 publications
15
456
4
2
Order By: Relevance
“…It has been observed to induce upregulation of HIF (Hypoxia Inducible Factor) which in its turn upregulates VEGF (vascular endothelial growth factor). 6 VEGF has been found to play an important role in the fracture healing response as well as in recruiting new vasculature. Recently, it has been demonstrated in an unimpaired, closed fracture healing model that injection of DFO at the injury can increase vascularity and bone volume at the fracture site.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed to induce upregulation of HIF (Hypoxia Inducible Factor) which in its turn upregulates VEGF (vascular endothelial growth factor). 6 VEGF has been found to play an important role in the fracture healing response as well as in recruiting new vasculature. Recently, it has been demonstrated in an unimpaired, closed fracture healing model that injection of DFO at the injury can increase vascularity and bone volume at the fracture site.…”
Section: Introductionmentioning
confidence: 99%
“…Desferoxamine, one of the most established iron chelators, activates HIF‐1 (hypoxia inducible factor 1) and induces high‐level expression of VEGF and erythropoietin mRNA 27, 28. Desferoxamine was also demonstrated to increase tubelike structure formation on Matrigel with human umbilical vein ECs 29. In addition, desferoxamine enhanced endothelial sprouting and vessel formation both in vitro and in vivo 29.…”
Section: Discussionmentioning
confidence: 95%
“…Desferoxamine was also demonstrated to increase tubelike structure formation on Matrigel with human umbilical vein ECs 29. In addition, desferoxamine enhanced endothelial sprouting and vessel formation both in vitro and in vivo 29. However, because iron is also a cofactor for oxidative phosphorylation and arachidonic acid signaling, a limitation of desferoxamine's translational potential is its off‐target effects 30.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that periosteum-derived cells are likely contributing to this reaction, as they are able to mount a strong pro-angiogenic and osteogenic response following exposure to hypoxia in vitro (Ichijima et al, 2012;van Gastel et al, 2012). In addition, activation of the HIF pathway also contributes to improved bone regeneration, as shown in a model of distraction osteogenesis, where enhanced hypoxia signalling in osteoblasts leads to better vascularization and bone regeneration in a VEGFdependent manner (Wan et al, 2008). Moreover, compounds that induce hypoxia signalling are reported to promote fracture healing in rodents (Shen et al, 2009;Wan et al, 2008).…”
Section: Hypoxia In Bone Repairmentioning
confidence: 99%
“…In addition, activation of the HIF pathway also contributes to improved bone regeneration, as shown in a model of distraction osteogenesis, where enhanced hypoxia signalling in osteoblasts leads to better vascularization and bone regeneration in a VEGFdependent manner (Wan et al, 2008). Moreover, compounds that induce hypoxia signalling are reported to promote fracture healing in rodents (Shen et al, 2009;Wan et al, 2008).…”
Section: Hypoxia In Bone Repairmentioning
confidence: 99%